Ground‐dwelling arthropod responses to succession in a pinyon‐juniper woodland. Issue 1 (16th January 2014) - Higgins, Jacob W.; Cobb, Neil S.; Sommer, Stefan; Delph, Robert J.; Brantley, Sandra L.
Abstract : Stand‐replacing wildfire is an infrequent but important disturbance in southwestern pinyon‐juniper woodlands. A typical successional cycle in these woodlands is approximately 300 years or more after a stand‐replacing fire. Arthropods, especially ground‐dwelling taxa, are one of the most abundant and diverse fauna in terrestrial ecosystems and are typically responsive to microhabitat change. Little is known regarding community responses of ground‐dwelling arthropods to changes in woodland successional stages from early ecosystems dominated by grasses, herbaceous plants, and fire adapted shrubs to tree‐dominated old‐growth ecosystems. In 2007 and 2008, within Mesa Verde National Park, Colorado, we compared the community composition of ground‐dwelling arthropods between old‐growth pinyon‐juniper stands that were 300–400 years old and early successional areas recovering from a stand‐replacing fire in 2002. The 2002 fire eliminated the dominant woody vegetation, which was replaced by increased herbaceous vegetation and bare ground. The early successional arthropod community showed a significantly higher abundance in major arthropod taxonomic groups, except spiders, compared to old‐growth woodland. Old‐growth species richness was greater in late August–September, 2007 and greater in early successional habitats during April–July, 2008. Spatial variability of the habitat was much greater in the recently burned early successional plots than the old‐growth late successional plots. The differences in habitat were strongly correlated with arthropod community composition, suggesting that ground‐dwelling arthropods are very sensitive to habitat changes. Habitat affiliation was strong, with 83% (early succession ruderal) and 91% (old‐growth woodland) of the species found primarily or exclusively in one habitat. Many habitat indicator species (defined as species found in significantly greater abundance in one habitat) were found in both burned and old‐growth habitats. Several species were found to be strict specialists exclusive to only one of these habitats. Collectively, the results suggest that heightened concern over loss of old‐growth woodlands is warranted, given the distinct nature of the ground‐dwelling arthropod community in old‐growth habitats.